Data model for smart electricity meter comprehensive verification based on BP neural network. Issue 2 (April 2020) - Wang, Qing; Dai, Yanjie; Wu, You; Liu, Yanxi; Wang, Tingting; Dong, Xianguang
Abstract: This paper proposes a BP neural network based model for smart electricity meter (SEM)comprehensive verification under variation conditions of temperature and humidity. Two-neuron BP neural network model and one-neuron BP neural network model are established, respectively. Theoretical results show that when temperature is fixed, the comprehensive verification error is rarely affected by humidity, whereas when humidity is fixed, the SEM comprehensive verification error has obvious variation with temperature which tends to linear correlation.